A phase IB study of durvalumab with or without tremelimumab and platinum-doublet chemotherapy in advanced solid tumours: Canadian Cancer Trials Group Study IND226. (May 2020) - Juergens, Rosalyn A.; Hao, Desiree; Ellis, Peter M.; Tu, Dongsheng; Mates, Mihaela; Kollmannsberger, Christian; Bradbury, Penelope A.; Tehfe, Moustapha; Wheatley-Price, Paul; Robinson, Andrew; Bebb, Gwyn; Laskin, Janessa; et al.
Highlights: Durvalumab and tremelimumab can be safely given with platinum-doublet chemotherapy. Tremelimumab and durvalumab exposures did not appear affected by chemotherapy. Efficacy in NSCLC is comparable to other immunotherapy/chemotherapy trials. Abstract: This multicenter phase Ib study aimed to establish a recommended phase II dose for durvalumab (Du) ± tremelimumab (Tr) in combination with standard platinum-doublet chemotherapy. Eligible patients were enrolled into one of six dose levels (DL) of Du ± Tr which included concomitant treatment with standard platinum-doublet regimens; (pemetrexed, gemcitabine, etoposide, (each with cisplatin or carboplatin) or nab-paclitaxel (with carboplatin)). Dose escalation was according to a Rolling Six type design. Both weight-based and fixed dosing of Du and Tr were explored. Du was continued until progression. Tr dosing was finite (up to 6 doses) with increasing dose and/or frequency by DL. 136 patients were enrolled. The majority of drug-related adverse events (AEs) were ≤ grade 2 and attributable to chemotherapy. AEs considered related to immunotherapy were mainly ≤ grade 2; the most frequent (occurring ≥10 %) were colitis/diarrhea, skin, and thyroid dysfunction. Seven patients had DLTs including pneumonitis, myocarditis, diarrhea, encephalitis, motor neuropathy, and enterocolitis. There were 2 treatment-related deaths. Tr and Du exposures did not appear affected by chemotherapy. Among the 73 non-small cell lung cancer (NSCLC) patients treated, the objective response rate was 51 % (95 %CI = 38.7–62.6 %) with a median progression-free and overall survival of 6.5 months (95 % CI = 5.5–9.4 months) and 19.8 months (95 % CI = 14.8 months – not yet reached) respectively. Anti-tumour activity was observed across PD-L1 subtypes. Du 1500 mg q3w and Tr 75 mg q3wx5 can be safely combined with platinum-doublet chemotherapy. Efficacy among NSCLC patients appears comparable to results from other immunotherapy and chemotherapy combination trials. NCT02537418